(untitled) (Research, Society and Development, 2021)
Obesity is a clinical condition characterized by excessive accumulation of fat in the body, considered a multifactorial genetic disease, aggravated by environmental, psychological, cultural, hereditary, dietary, hormonal and metabolic factors. This research aims to discuss obesity in adolescence during school years through a literature review. As a methodological process, it is a simple narrative review study. The data collection for this study was made from a bibliographic survey through electronic search of articles indexed in Scielo, Google Scholar, Lilacs, reliable sites, Ministry of Health manuals. As results presented, it can be noted that , in recent years, there has been a large number of cases of obesity in childhood and adolescence. Several researches point out that this sudden increase in obesity may be associated with several contributing factors such as: bad eating habits, physical inactivity, genetic factors, socioeconomic level and emotional factors. Studies show that genetic factors have a major influence on the increase in obesity, which is a complex and heterogeneous disease. It is important to note that genetic factors alone do not explain weight gain. Thus, the combination of genes with the factors mentioned above are involved in the development of the most common forms of obesity. Several treatments were mentioned during this review, with physical activity in adolescence together with SEM having a fundamental role in the treatment and prevention of obesity.